DETERMINAN MINAT MAHASISWA BERINVESTASI DI PASAR MODAL - Hidayat, Rahmat; Nainggolan, Edisah Putra (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to analyse the factors that influence students' interest in investing in the capital market. The determining factors are education, risks and profits, and availability of funds. The analysis technique used is the Structural Equation Model (SEM) with the Smart PLS V. 3.2 application tool. The research results show that education has a positive and significant effect on students' interest in investing in the capital market. Education, both formal and non-formal, will encourage students' understanding of the importance of investment, both in the capital market and investment in other sectors. Profits and risks have a positive and significant effect on students' interest in investing in the capital market. Profits will encourage students' interest in investing in the capital market. This is the main factor that attracts students' interest. The source of funds has a positive and significant effect on students' interest in investing in the capital market. Students who have excess sources of funds or have sources of income tend to be more interested in investing in the capital market. Conversely, if students do not have excess sources of funds, they will choose the safe route by not investing in the capital market.